Development of metal dopedhydroxyapatite for bone implant application - Syed Abu Bakar, Sharifah Adzila (2014)
Hydroxyapatite (HA) powder with nanosize particles was successfully synthesized by mechanochemical method in a dry state at 170 rpm, 270 rpm and 370 rprn rotation speeds in 15 hours respectively. The research revealed that among the three rotation speeds employed, 370 rpm synthesized powder showed better characteristics as determined by X-ray Diffraction (XRD), Fourier Transform Infra Red (FTIR) and Field Emission Scanning Electron Microscopy (FESEM) analyses. Similarly, the sintering properties of these powders showed maximum densification, Vickers hardness and fracture toughness with values of 96.8%, 5.29 GPa and 1.49 M~a.m"~re,s pectively were obtained when sintered at 1250°C. The rotation speed of 370 rpm was subsequently employed to prepare the Na-doped HA and Mg-doped HA. The study found that the decrease of the XRD peak intensities and the decrease of FTIR adsorption bands corresponded to HA phase were related to the increase of Na' and M~io~ns' concentration. The substitution of the ions also changed the lattice parameters, the unit cell volumes and the crystal size of HA. Sintering and ion doping also influenced the stability of the HA phase where the decomposition occurred between 1000°C-1300°C sintering temperature and with increasing Na' and M~io~ns c+on centration in the HA lattice. This has led to the increase of HA phase decomposition due to Na+ and Mg2' replacing the ~a'+ sites. Increasing sintering temperature has led to the decrease of relative densities, Vickers hardness and fracture toughness of undoped HA, Na-doped HA and Mg-doped HA. The 1% Na-doped HA was found to have maximum densification and Vickers hardness of 99.2% and 5.47 GPa, respectively when sintered at 1250°C. The 1% Na-doped HA also exhibited a high fracrure toughness of 1.84 ~~a-rnw'h"e n sintered at 1300°C. Na' doping was more effective in enhancing the mechanical perforn~ance of HA compared to ~g'+ doping. Na-doped HA and Mgdoped HA increased the biocompatibility of HA as the maximum growth of calcium phosphate was significantly shown in the 7% Na-doped HA after 7 days of exposure. However. osteoblast cell culture showed that increasing Na' and M~"co ncentration to 7% - 9% molar concentration induced the formation of dead cells near to the samples. The study found that Na' and M~"in higher molar concentration particularly 9% doping was detrimental as it affected the mechanical properties as well as the biocompatibility of the hydroxyapatite ceramic.